2014
DOI: 10.1111/pbi.12190
|View full text |Cite
|
Sign up to set email alerts
|

High‐throughput fluorescence‐activated cell sorting for lipid hyperaccumulating Chlamydomonas reinhardtii mutants

Abstract: SummaryThe genetically tractable microalga Chlamydomonas reinhardtii has many advantages as a model for renewable bioproducts and/or biofuels production. However, one limitation of C. reinhardtii is its relatively low-lipid content compared with some other algal species. To overcome this limitation, we combined ethane methyl sulfonate mutagenesis with fluorescence-activated cell sorting (FACS) of cells stained with the lipophilic stain Nile Red to isolate lipid hyperaccumulating mutants of C. reinhardtii. By m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 31 publications
1
33
0
Order By: Relevance
“…Previous reports often qualitatively describe lipids by the NR staining method [4547]. By combining the conventional methods and the fluorometric staining using NR, this study identified linear regression equations with high goodness of fit between FI and the oil-yielding performance indexes (i.e., TL content, TAG content, and biodiesel production) (Table 3).…”
Section: Discussionmentioning
confidence: 86%
“…Previous reports often qualitatively describe lipids by the NR staining method [4547]. By combining the conventional methods and the fluorometric staining using NR, this study identified linear regression equations with high goodness of fit between FI and the oil-yielding performance indexes (i.e., TL content, TAG content, and biodiesel production) (Table 3).…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies have assessed the responses of metabolic genes and proteins under non-steady state conditions when TAG accumulates (Miller et al, 2010;Boyle et al, 2012;Msanne et al, 2012;Blaby et al, 2013;Wase et al, 2014) or identified mutants that are defective for TAG accumulation or catabolism (Li et al, 2012;Boyle et al, 2012;Tsai et al, 2014;Xie et al, 2014;Ngan et al, 2015;Kajikawa et al, 2015). The relationship between starch synthesis and TAGs has also been investigated, and it appears that fixed carbon can be shunted toward TAGs when starch synthesis is blocked (Li et al, 2010a(Li et al, , 2010bWork et al, 2010;Siaut et al, 2011;Goodenough et al, 2014).…”
Section: Insps As a Metabolic Signal For Carbon Metabolismmentioning
confidence: 99%
“…The occurrence and formation of LDs can be traced easily by microscopic examination or through flow cytometry, taking advantage of the lipophilic property of dyes such as Nile red or Bodipy (Cagnon et al 2013;Greenspan et al 1985;Mou et al 2012;Xie et al 2014;Yan et al 2013;Zhang et al 2014). Structure of LDs has been studied under Confocal fluorescent or Transmission Electron Microscopes (TEM) (Fig.…”
Section: Occurrence Formation and Dynamicsmentioning
confidence: 99%